Reactions to ethnic deviance the role of backlash in racial stereotype maintenance. [article]. - Phelan, Julie E.
Backlash effects are social and economic penalties for counterstereotypical behavior (Rudman & Phelan, 2008). Five experiments support a model of the role of backlash in racial stereotype maintenance from the standpoint of perceivers and actors (Rudman & Fairchild, 2004). In experiment 1, perceivers sabotaged Asians and Whites for succeeding in counterstereotypical domains, thereby preventing their future success. In experiment 2, a White rapper suffered prejudice and economic discrimination, relative to a Black rapper, and prejudice mediated discrimination. Further, actors threatened by backlash for achievement in cross-racial domains responded to success in ways that bolster ethnic stereotypes. For example, Black men and women who feared backlash for academic skill (Experiment 3), and non-Black(Experiment 4) and non-White (Experiment 5) men who experienced backlash for cross-racial achievement, resorted to defensive startegies that preserve racial stereotypes (e.g., refusing to publicize and pursue counterstereotypical talents). Implications for cultural stereotype maintenance are discussed. -- (from the author)
Keywords: Social cognition; Stereotypes; Stereotype maintenance; Impression information; Backlash